Aplicación de la metodología seis sigma para el control de variación en el envasado de pinturas - Barcia Villacreses, Kléber (2010)
The customer is the main reason for a company and customer satisfaction is the only way to secure sales and strengthening and maintaining our market." Therefore, in addition to a high quality paint, Paints ABC is constantly looking to generate greater value for its clients and in that search, it wants security and customer confidence in its products is the basis for affirming a sense strengthened membership. Based on an objective set and reviewed, stands a database, with the database are developed Pareto diagrams , and is obtained as a result, the focus on manual packaging process, which presents greater variation and is the 70 % of existing packaging process. A priority is to standardize the process, to ensure the elimination and / or control of noise variables affecting the results, during the process, it makes the separation of the plant into two parts, one for Oil-based production and one for Water-based. Initially amending two workstations, one in the water-based production line and one in the oil-based production line, the results of the new process is replicated at all filling stations of both plants, for a total of eight workstations